How does El Niño Southern Oscillation impact the wind resource in Chile? A techno-economical assessment of the influence of El Niño and La Niña on the wind power. (April 2017) - Watts, David; Durán, Pablo; Flores, Yarela
Abstract: This paper assesses the impact of the El Niño Southern Oscillation (ENSO) on the wind speed, energy production, as well as its impact on the value of potential wind projects at different sites across Chile. The study applies cyclostationary empirical orthogonal function (CSEOF) analysis to isolate the ENSO influence on the wind speed, and therefore on the energy output of nearly all current and potential wind farms in Chile. Finally, a review of techno-economical parameters is made to assess the economic impact of an ENSO event occurring at different years in the lifetime of a wind energy project. The main contribution of this work is to establish the locations in Chile where this climatic oscillation is important for the system planning, the energy forecasting and the risk assessment. Graphical abstract: Highlights: The effect of El Niño and La Niña on wind speed and power generation is modelled. Important wind development areas in Chile are highly sensitive to ENSO. Changes in the value of wind projects caused by ENSO is estimated. The effect of El Niño could change an investment decision for a wind project. ENSO is important for forecasting, supply contracts and systems operation.